Nurses' Knowledge of Adverse Medication Events and its Contributing Factors at Intensive Care Units: A Cross-Sectional Study - Rasha Allehebi; Laila Hamed (Evidence-Based Nursing Research)
Context: Medication errors are a major concern in the healthcare setting, as they result from the inappropriate use of products related to the treatment or the effects that lead to harm. In Saudi Arabia, prescription errors constitute nearly one-fifth of all medication errors. Still, there is a difference in dealing with the process of using medications based on each country and its background.